A culture of care: How Lotus House Women's Shelter heals program participants through genuineness, space, high expectations, dignity, individualized attention, and community. Issue 4 (6th May 2021) - Eaton, Asia A.; Stephens, Dionne P.; Ruvalcaba, Yanet; Banks, Jasmine; ,
Abstract: The present study was designed to examine perceptions of Lotus House Women's Shelter from the perspective of former program participants, for the purpose of informing shelter programming and policies. Our qualitative research followed a community‐based participatory research framework. Fifty diverse women graduates of Lotus House Women's Shelter participated in eight focus groups to discuss their experiences with Lotus House and other shelters. Findings from this study highlight the elements that create a "culture of care" within an organization. Participants described Lotus House shelter culture as genuine, defined by dignity and respect, having high expectations for guest independence and accountability, giving space to rest and recuperate, recognizing and accommodating individual needs and experiences, and fostering a sense of community. Creating an organizational "culture of care" is an avenue by which any shelter or related organization can enhance the experience of program participants.